An Integrated In Silico Approach to Develop Epitope-Based Peptide Vaccine Against SARS-CoV-2 - Garg, Prekshi; Srivastava, Neha; Srivastava, Prachi (Coronaviruses, 2022)
Background: SARS-CoV-2 has been a topic of discussion ever since the beginning of 2020. Every country is trying all possible steps to combat the disease ranging from shutting the complete economy of the country to the repurposing of drugs and vaccine development. The rapid data analysis and widespread tools have made bioinformatics capable of giving new insights to deal with the current scenario more efficiently through an emerging field, vaccinomics. Objective: The present in silico study was attempted to identify peptide fragments from spike surface glycoprotein of SARS-CoV-2 that can be efficiently used for the development of an epitope- based vaccine designing approach. Methods: The epitopes of B and T-cell are predicted using integrated computational tools. VaxiJen server, NetCTL, and IEDB tools were used to study, analyze, and predict potent T-cell epitopes, their subsequent MHC-I interactions, and B-cell epitopes. The 3D structure prediction of peptides and MHC-I alleles (HLA-C*03:03) was further made using AutoDock4.0. Results: Based on result interpretation, the peptide sequence from 1138-1145 amino acid and sequence WTAGAAAYY and YDPLQPEL were obtained as potential B-cell and T-cell epitopes, respectively. Conclusion: The peptide sequence WTAGAAAYY and the amino acid sequence from 1138-1145 of the spike protein of SARS-CoV-2 can be used as a probable B-cell epitope candidate. Also, the amino acid sequence YDPLQPEL can be used as a potent T-cell epitope. This in silico study will help us identify novel epitope-based peptide vaccine targets in the spike protein of SARS-CoV-2. Further, the in vitro and in vivo study needed to validate the findings.
Keywords: peptide vaccine